PENGUKURAN KINERJA DI YAYASAN HPI MENGGUNAKAN BALANCED SCORECARD (AHP) DAN ANALYTIC HIERARCHY PROCESS (AHP) - Suprihadi, Deni; Suharyanto, Suharyanto (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2023)
In the complicated and growing fast education environment now, we need effective performance measurement methods and able to measure education institution properly. Method which able to apply is Balance Score Card (BSC), which it considers aspects of human resources, system used in, operating process, finance, and customer satisfactions. The result of performance measurement of HPI institution gives 14 strategic targets, quality improvement, widening network, optimization income and efficiency of operating cost, effective investments, research and innovations, time of service reduction, human resource empowerment, teachers effectiveness of teaching process, satisfaction and improvement of mentality of employees, and good information system. Scoring of OMAX performance indicator give point 4.538 or level 4-7 yellow color (middle performance). The performance of the institution is below the targets and need improvements to meet targets. The productivity index is 18,3% or increase 18,3% from period before.